Solitary lag-screw fixation for mandibular angle fractures: Prospective study - Sasikala Balasubramanian; C Kumaravelu; P Elavenil; V B Krishnakumar Raja (Wolters Kluwer Medknow Publications, 2014)
Aim: The aim of the prospective clinical study was to evaluate the efficacy of "solitary lag-screw fixation" in treating mandibular angle fractures. Materials and Methods: Five cases of mandibular angle fracture were taken up for the study. All cases were treated with solitary lag-screw technique according to principles outlined by this technique using 2.7 mm stainless steel screws. Postoperative complications such as wound dehiscence, infection, neurosensory disturbance, mal-occlusion, nonunion, and postoperative mouth opening were recorded for follow-up of 6 months. Observation and Results: The patients were evaluated postoperatively for 6 months. All the cases achieved long-term occlusal stability, interincisal opening of 35-45 mm, and showed no signs of infection or neurosensory disturbance. Conclusion: Solitary lag-screw fixation is an effective and simple procedure in producing good treatment results for angle fractures of mandible, but is technique sensitive and requires surgical expertise.